National Geographic : The Photographs - Bendavid-Val, Leah (Washington, D.C National Geographic Society, 1991)
Photographs from the archives of "National Geographic" share an array of work reflecting the themes of The Land, Underwater, Science, The United States, and The World--by some of the world's finest photographers.
Include Color Illustration
Keywords: Travel photography